Identification of the characteristic components in walnut and anti-inflammatory effect of glansreginin A as an indicator for quality evaluation. Issue 1 (2nd January 2020) - Haramiishi, Rie; Okuyama, Satoshi; Yoshimura, Morio; Nakajima, Mitsunari; Furukawa, Yoshiko; Ito, Hideyuki; Amakura, Yoshiaki
ABSTRACT: Walnut is a nutritious food material, but only a few studies have been conducted on the mechanisms of its functions and the technique for quality evaluation. Therefore, we analyzed the components in aqueous methanol extract of walnut, and characterized 30 components, including three new compounds, glansreginin C, ellagic acid 4- O -(3′- O -galloyl)-β-D-xyloside, and platycaryanin A methyl ester. We analyzed the extracts of other nuts using HPLC and clarified that a characteristic peak corresponding to glansreginin A was mainly observed in walnut. These results suggested that glansreginin A might be an indicator component of the quality of walnut. We then examined whether glansreginin A has neuroprotective effect, using lipopolysaccharide (LPS)-induced inflammatory model mice. The results revealed that oral administration of glansreginin A prevented LPS-induced abnormal behavior and LPS-induced hyper-activation of microglia in the hippocampus. These results suggested that glansreginin A has the ability to exert neuroprotective effect via anti-inflammation in the brain. Graphical abstract: : Glansreginin A might be an indicator of quality of walnut products, and it has the ability to exert neuroprotective effect via anti‐inflammation in the brain.